An exploration of prenatal breastfeeding self-efficacy: a scoping review protocol [version 3; peer review: 2 approved] - Liz McGovern; Fionnuala McAuliffe; Aisling Geraghty; Sharleen O'Reilly (Open Research Europe, 2023)
Objective: To synthesise the evidence on prenatal breastfeeding self-efficacy, including identifying concepts and theoretical frameworks that underpin its development, the evidence on its measurement, interventions used to improve it, and association with breastfeeding outcomes. Background: Breastfeeding self-efficacy is described as a woman’s self-belief and confidence in her perceived ability to breastfeed. It is a modifiable measure that is strongly associated with breastfeeding outcomes such as initiation, exclusivity, and duration. Interventions aimed at increasing self-efficacy are often in the postnatal period and have been shown to be effective at improving breastfeeding outcomes. The prenatal period appears to be underexplored in the literature and yet focusing on enhancing it may have the potential for further improvements in self-efficacy and on subsequent breastfeeding outcomes. A comprehensive knowledge synthesis on prenatal breastfeeding self-efficacy is lacking. Methods: The search will include databases across health, psychology, sociology, and the grey literature on breastfeeding guidance. Once the PCC framework (Problem: breastfeeding, Concept: self-efficacy, Context: prenatal period) is met, sources of evidence from any contextual setting will be eligible for inclusion. Limits will not be applied on geographic location or year of publication. The PRISMA-ScR flow diagram of search and study selection will be used to report final figures. Two independent reviewers will perform title and abstract screening and full text review. Data will be charted to provide a logical and descriptive summary of the results that align with the objectives. Conclusion: The results will provide an understanding of what has been done in the space and what gaps exist, informing recommendations for the timing of measurement and the design of prenatal interventions.